Imagining Home: Performing Adoptability in Transnational Canine Rescue and Rehoming - Schuurman, Nora (Humanimalia, 2022)
This article explores online performances of adoptability of homeless dogs in transnational animal rescue and rehoming practices in Finland, based on an analysis of the websites of Finnish animal rescue charities, as well as interviews with volunteers at these charities. Drawing on recent work on concepts such as home, care, encounter value, and nonhuman charisma, I explore how homeless dogs in other countries are portrayed online for the purpose of transnational rehoming as pets and, more generally, how animal adoptability and ideals of a pet and a multispecies home are constructed. The dogs’ life histories, present situation, and subsequent adoptability are validated in stories based on interpretations of their past and present experiences, subjectivity, and agency. The encounter value of homeless dogs is based not only on the positive affects their portrayals are supposed to evoke, but also on interpretations of their experiences of suffering and the compassion they may elicit in the potential adopter. The adoptability of these dogs, I argue, is constructed on an encounter value based on compassion-evoking charisma rather than promises of sharing a life with an “ideal” pet and their rehoming is presented as an opportunity to create a home with an animal who may never have had one before.